Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Using the equation of the hyperbola, it is found that the statement is false.
Equation of an hyperbola:
The equation of an hyperbola of center [tex](x_0,y_0)[/tex] is given by:
[tex]\frac{(x - x_0)^2}{a^2} + \frac{(y - y_0)^2}{b^2} = 1[/tex]
The foci are given by: [tex](x_0 - c, y_0)[/tex] and [tex](x_0 + c, y_0)[/tex].
In which [tex]c^2 = a^2 + b^2[/tex]
In this problem, we have that the parameters are given by:
[tex]x_0 = 2, y_0 = -1, a^2 = 36, b^2 = 64[/tex].
Then:
[tex]c^2 = a^2 + b^2[/tex]
[tex]c^2 = 100[/tex]
[tex]c = 10[/tex]
The foci are given by:
[tex](x_0 - c, y_0) = (2 - 10, -1) = (-8, -1)[/tex]
[tex](x_0 + c, y_0) = (2 + 10, -1) = (12, -1)[/tex]
Hence, the statement is false.
To learn more about equation of the hyperbola, you can take a look at https://brainly.com/question/20776156
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.